Mykhailo Mukhyn and the journal “Nova Ukraina”: pseudonyms and cryptonyms - Vlasenko, Valeriy (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2023)
Purpose. This study aims to integrate the pseudonyms and codenames used by the renowned Ukrainian journalist and literary critic, Mykhailo Mukhyn, into scholarly discourse. These aliases were employed by Mukhyn during the publication of his materials in the pages of the Prague-based journal "Nova Ukraina" (1922-1928).Methodology. The research methodology is grounded in the scientific principles of historicism, objectivity, and systematic analysis. Employing general scientific methods such as analysis, synthesis, induction, deduction, and comparison, as well as specialized historical methods like historical-comparative, historical-typological, and biographical approaches, alongside source-critical methods including archeographic and archival heuristics and source criticism, the study successfully identified, analyzed, and introduced into scholarly circulation a letter from Mykhailo Mukhyn. This letter played a crucial role in determining his pseudonyms and codenames.Scientific novelty. The introduction of Mykhailo Mukhyn's letter to the co-editor of the journal "Nova Ukraina," Mykyta Shapoval, facilitated the clarification of Mukhyn's pseudonyms and codenames, consequently attributing authorship to numerous materials published in the journal.The relevance. The significance arises from the author's goal of defining the creative legacy of journalist and literary critic Mykhailo Mukhyn within the pages of the journal "Nova Ukraina," co-edited by Mykyta Shapoval and Volodymyr Vynnychenko.Conclusions. The examination and publication of Mykhailo Mukhyn's letter to Mykyta Shapoval dated March 29, 1926, provided insight into the broad and diverse spectrum of Mukhin's creative contributions to the Prague-based journal "Nova Ukraina". In addition to Mukhyn's publications signed with his own name, the periodical featured numerous articles, reviews, critiques, and announcements under pseudonyms such as "Kyіanyn", "K.", "K-n" or without a signature.